Development, validation and reliability of Schizophrenia Stage Inventory (SSI) - Mohammad Aziz Shah Mohamed Arip (Tanjong Malim, 2021)
Development, validation and reliability of Schizophrenia Stage Inventory (SSI) by Mohammad Aziz Shah Mohamed Arip